Senorita Pool Cafe / Noradinah Papartaim... [et al.] - Jonathan D., Katrina; Gomboyon, Vivian Dani; Edward, Beverly Branda; Sadon, Sharifah Nadzerah; Papartaim, Noradinah (2013)
Our business, Senorita Pool Cafe is a business that provides a Pool Games services especially for female. This is the services that we provide in our business, we also provide a manicure & pedicure, Cafe, and also a karaoke session. We start to invent this kind of business because there is less number of female involve in pool games. It is because they are shy to play pool games since there are a lot of male rather than female in a pool centre. We encourage the female to involve in pool sports because pool sports is a unique sports which it need the players to apply strategies and skills to play. Senorita Pool Cafe is combinations of 3 different words which are the "Senorita" are from Spanish word which means female. While Pool is the main services of our business and Cafe is to describe that we also provide a food and beverages services The Location for our business is at 1 Sulaman. We chose 1 Sulaman at Sepanggar as our location because there are multiple educational institution and housing areas. Besides that, this locations is located to the nearest the biggest shopping mall at Sabah, 1 Borneo.